Dietary Patterns, Socioeconomic Status, and Risk of Type 2 Diabetes in the Sister Study. (14th June 2022) - Crawford, Brittany; Sandler, Dale; Merchant, Anwar; Steck, Susan; Park, Yong-Moon
Abstract: Objectives: Higher diet quality is associated with decreased risk of type 2 diabetes (T2D). Socioeconomic status (SES) has been associated with measures of diet quality. However, few studies have investigated whether the association between diet quality and T2D differs by SES. Methods: We used prospective cohort data from 41, 280 Sister Study participants aged 35 to 74 years who enrolled in 2003–2009 and were followed until September 2017. The alternate Mediterranean diet (aMED), Dietary Approaches to Stop Hypertension (DASH), alternative Healthy Eating Index (aHEI), and Healthy Eating Index 2015 (HEI-2015)] scores were calculated using baseline data from a 110-item Block food frequency questionnaire previously validated in women. SES was evaluated by individual and neighborhood levels. The Area Deprivation Index (ADI), a census-based index was used to define neighborhood SES. Incident T2D was defined based on self-reported physician's diagnosis of T2D or use of anti-diabetic medications on annual follow-up questionnaires. Multivariable-adjusted hazard ratios (aHRs) and 95% CIs were estimated using Cox proportional hazards models with age as the primary time scale. Effect modification was evaluated by stratification and including an interaction term in statistical models. Results: Inverse associations between dietary pattern scores and incident T2D were observed across all four dietary indices after adjustment for potential confounders (aMED: aHRQ4vsQ1 : 0.64, 95% CI: 0.56, 0.72; DASH: aHRQ4vsQ1 : 0.55, 95% CI: 0.49, 0.62; aHEI: aHRQ4vsQ1 : 0.54, 95% CI: 0.48, 0.61; aHEI-2015: HRQ4vsQ1 : 0.61, 95% CI: 0.55, 0.69). The inverse association between all four dietary indices and T2D risk was most pronounced among women with higher education and income. The inverse association between HEI-2015 and T2D risk was strongest among women with lower ADI (low ADI aHRQ4vsQ1 : 0.49, 95% CI: 0.39, 0.61; high ADI aHRQ4vsQ1 : 0.70, 95% CI: 0.58, 0.85; pinteraction : 0.003). Estimates from aMED, DASH, and aHEI models were similar. Conclusions: Our findings suggest that healthy eating patterns may reduce the risk of T2D and may have a greater impact among participants with higher individual SES and lower neighborhood deprivation. Funding Sources: National Institute of Environmental Health Sciences T32 from NIH-NIGMS